Kinetics of BTX Removal by Rhodococcus Erythropolis in a Slurry Bioreactor - Ole, Maria Assumpta Nogo; Ranggina, Dian; Pampang, Harun; Darajat, Zakiyah (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Benzene, toluene, and xylene (BTX) contamination arising from oil-drilling operations constitutes a persistent environmental challenge, necessitating the development of robust bioremediation strategies underpinned by kinetic evaluation. This study systematically investigated the kinetics of BTX removal by Rhodococcus erythropolis in a slurry-phase bioreactor employing soil sourced from the PPEJ oil-drilling site in Tuban, Indonesia, with particular emphasis on the influence of inoculum concentration on the k₀ and the Kₘ. Batch experiments were conducted at inoculum loadings of 12,5%, 15%, and 17,5% (v/v), with periodic monitoring of dissolved-phase BTX concentrations and BOD. Analytical methodologies encompassed gas chromatography–mass spectrometry (GC–MS) for the quantification of BTX and intermediate metabolites, BOD assessment, and kinetic modeling to estimate k₀ and Kₘ values. The results demonstrated that incremental increases in inoculum concentration consistently elevated the k₀, thereby expediting BTX removal in reactors with higher biomass. However, a concomitant decline in specific activity per unit biomass was observed at the highest inoculum level, attributable to mass-transfer limitations—specifically, restricted diffusion of oxygen and substrate into microbial flocs—and heterogeneity in enzyme induction. The estimated Kₘ values exhibited variability across inoculum concentrations, indicating that substrate affinity is modulated by reactor physical parameters and microbial enzymatic adaptation. These findings underscore the necessity of optimizing inoculum concentration in concert with operational parameters such as dissolved oxygen control, agitation intensity, and structured kinetic assays to ensure that enhancements in k₀ are translated into effective per-cell degradation and complete mineralization of BTX contaminants in soils impacted by oil-drilling activities.